2019
DOI: 10.1177/1178630219839013
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Mitochondrial-Nuclear Cross Talk in Lymphocytes Exposed to Landfill Leachate

Abstract: Landfill leachate, a complex mixture of different solid waste compounds, is widely known to possess toxic properties. However, the fundamental molecular mechanisms engaged with landfill leachate exposure inducing cellular and sub-cellular ramifications are not well explicated. Therefore, we aim to examine the potential of leachate to impair mitochondrial machinery and its associated mechanisms in human peripheral blood lymphocytes. On assessment, the significant increase in the dichlorofluorescein (DCF) fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Melanoma cells, as cancerous cells, are more resistant to oxidative stress and their proliferation rate is enhanced through the activity of ROS. The literature data point to the fact of the induction of oxidative stress in human cells by leachate (Gupta et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma cells, as cancerous cells, are more resistant to oxidative stress and their proliferation rate is enhanced through the activity of ROS. The literature data point to the fact of the induction of oxidative stress in human cells by leachate (Gupta et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have reported that exposure to different environmental toxins including air pollutants considerably affects mitochondrial redox machinery. 22,23 In the present study, we investigated the mitochondrial-mediated epigenetic regulation in peripheral lymphocytes following exposure to a carcinogenic (BaP) and noncarcinogenic (ANT) PAHs, an important class of air pollutant. Overall, our findings suggest that exposure to ANT induces mitochondrial toxicity with no significant epigenetic alteration, while BaP disturbs the redox machinery and initiates a cascade of aberrant epigenetic modifications that include changes in the expression of mitochondrial miRNAs, DNA hypomethylation, and modification in histone tails.…”
Section: Discussionmentioning
confidence: 99%
“…The mean fluorescence intensity of the cells was then analyzed through flow cytometry (Attune NxT). 22 For assessment of mitochondria-mediated apoptosis, caspase-3 activity was measured in cells using the caspase-3 apoptosis kit. Briefly, the cells were washed and fixed for 20 minutes on ice.…”
Section: Dna Damage and Apoptosismentioning
confidence: 99%
“…The GAPDH was used as an internal control. Ct values were recorded, and fold change was calculated by using ddCt method [17].…”
Section: Methodsmentioning
confidence: 99%